2018
DOI: 10.1111/rda.13143
|View full text |Cite
|
Sign up to set email alerts
|

Specific fetometric formulas ofICCandBPfor calculating the parturition date in the miniature breeds of canine

Abstract: The aim of this study was to derive the growth curves of the inner chorionic cavity and the biparietal distance in miniature dog breeds by ultrasonographic fetometry and present new specific formulas for prediction of parturition date. In this study, foetal biometry parameters were obtained using serial ultrasonographic examinations in 24 pregnant bitches of six different miniature breeds (≤5 kg). The mating time was unknown. Overall, 25 inner chorionic cavity diameter (ICC) and 22 biparietal diameter (BP) mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
6
1
Order By: Relevance
“…The author suggests that formulas used for small and medium-sized breeds, such as those described by Luvoni and Grioni (2000) might be used in female dogs of miniature breeds. The regression formula (y = 1.6190 × BPD -39.70) presented in the study (Socha and Janowski, 2018) differs from the formula presented in this research and features a large variation of the values found for the Chihuahua, which highlights the need to study this breed individually and to standardize an adequate calculation.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…The author suggests that formulas used for small and medium-sized breeds, such as those described by Luvoni and Grioni (2000) might be used in female dogs of miniature breeds. The regression formula (y = 1.6190 × BPD -39.70) presented in the study (Socha and Janowski, 2018) differs from the formula presented in this research and features a large variation of the values found for the Chihuahua, which highlights the need to study this breed individually and to standardize an adequate calculation.…”
Section: Discussioncontrasting
confidence: 64%
“… Socha and Janowski (2018) found a correlation of 0.94 ( P< 0.05) of the BPD with the DBP in miniature dog breeds. The author suggests that formulas used for small and medium-sized breeds, such as those described by Luvoni and Grioni (2000) might be used in female dogs of miniature breeds.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Litter size does not seem to have an influence on accuracy of gestational ageing and parturition date prediction (Kutzler, Yeager, et al., 2003 ). On the other hand, body size and/or breed‐specific formulas or corrections to maternal body weight should be used to achieve the most accurate prediction of gestational age or parturition day (Cecchetto et al., 2017 ; Lopate, 2008 , 2018 ; Luvoni & Grioni, 2000 ; Sananmuang et al., 2021 ; Siena & Milani, 2021 ; Socha & Janowski, 2018 ; Son et al., 2001 ; de Albuquerque Vieira et al., 2020 ; Yeager et al., 1992 ).…”
Section: Introductionmentioning
confidence: 99%